Structural characterization of SiC nanoparticles *Project supported by the National Natural Science Foundation of China (No. 11505273) and the Strategic Priority Research Program of the Chinese Academy of Sciences (No. XDA02000000). (October 2017) - Sun, Baoxing; Xie, Ruobing; Yu, Cun; Li, Cheng; Xu, Hongjie
Abstract: The structure and size of SiC nanoparticles were studied by different characterization methods including small angle X-ray scattering (SAXS), transmission electron microscope (TEM), and X-ray diffraction (XRD). The results showed that particle size distributions determined respectively from SAXS and TEM are comparable and follow the log-normal function. The size distribution of the particles is between 10 to 100 nm with most of them being in the range of 20–50 nm. The average particle size is around 42 nm. XRD identifies the phase of the SiC nanoparticles and suggests the average size of the single crystalline domain to be around 21 nm. The combined results from XRD and SAXS suggest the existence of many polycrystals, which is confirmed by the HRTEM observation of particles with twins and stacking faults. The material synthesis methods leading to various particle sizes are also discussed.